Assessing the Functionality and Effectiveness of the Departments of Agriculture in the Northern Region under the Local Government Service. - Tahiru, J.A. (University of Ghana, 2018)
The local Government Service Act 203 of L.I 1961, was passed in 2011 and as part of its implementation, extension services at the local level was ceded to the local government service and Departments of Agriculture became units under the Metropolitan, Municipal and District Assemblies. Given the importance of extension in agricultural development at the local level, this research aimed to assess the functionality and effectiveness of Departments of Agriculture under the Local Government Service, using the Northern Region as a case study. The research objectives were to, assess the human and physical resource gaps of the DOAs; assess the incentives to motivate staff of DOAs; assess the priorities given to DOA activities in the LGS planning; and elicit perceptions of staff of DOAs about the functionality and effectiveness of the feedback mechanisms between DOAs and the District Assemblies. This is a qualitative study; the analytical instruments are ranking of responses with a Likert scale and t-tests of differences between mean scores. A probit regression is also estimated to explain staff perceptions about prioritisation of DOA activities by the District assemblies. The data includes primary and secondary data. Secondary data was collected from published and unpublished works as well as from formal interactions with core officers of the departments. Primary data was collected from a sample of 140 staff of the DOAs, the planning and budget units of the District Assemblies, and the regional Director of Agriculture. To identify resource gaps, the actual capacities of DOAs were compared with the expected capacities in relation to the available resources. The study identifies gaps in staff numbers, technical qualification, office space and equipment. Incentive levels for staff are low in comparison to the centralised governance system under the Ministry of Food and Agriculture. Though opportunities for trainings and promotions are better under the LGS, majority of respondents held the perception that level of staff development under the LGS is lower, compared to the centralized system. Staff perceive very low priority being given to DOAs in the planning activities of District assemblies. Monitoring and accountability are assessed by staff perception about the effectiveness of feedback mechanisms in terms of reporting. Relationship with the regional directorate is weaker because the regional office does not provide the needed technical backstopping. The monitoring and evaluation under LGS is also weaker than under the centralised governance. Majority of district assemblies do not have the agriculture sub-committee, which has been valuable to DOAs. Districts with this committee have benefitted from advocacy, resource mobilisation among others. Conclusions are that, there is wide resource gaps in the DOAs; DOAs are not well integrated into the District Assembly, as exemplified by the absence of the agriculture sub-committee in most districts studied; the weak relationship between the DOAs and the regional Department of Agriculture has the tendency of further weakening the former’s technical abilities; poor accountability and feedback checks can result in poor monitoring and evaluation of the performance of the DOAs. It is recommended that the Ministry of Local Government and Rural Development, in collaboration with MoFA should monitor the extent to which the DOAs are integrated into the decentralization system and recognized as integral part of the local Assembly. Areas to monitor should include, resource allocation, staff promotion and training, planning and implementation of programmes and activities, and a working monitoring and accountability system for efficient resource use. It is also recommended that the district assemblies should be given orientation to sensitise them to the technical nature of the DOAs. The two ministries should develop a document that lays down appropriate steps for the DOAs and Regional Departments of the agriculture to follow to improve the functional inter-relationship between the two. The LGS should prioritise the establishment of the agriculture sub-committee in all the District Assemblies. Finally, staff development programmes should be developed by the DOAs and LGS for capacity building.
MPhil.
Keywords: Agriculture; Northern Region; Local Government Service